Application of polysaccharide-rich solution derived from waste macroalgae Enteromorpha prolifera in cherry tomato preservation and utilizing post-extraction residue for crude bio-oil production. (30th May 2023) - Wu, Yijing; Xu, Xin; Jiang, Xuanjing; Liu, Shuji; Lin, Jingying; Lin, Xiaoyu; Zhang, Yange; Shi, Chuanyang; Zhao, Chao; Yang, Jie
Graphical abstract: Highlights: Using water-soluble polysaccharide derived from waste macroalgae as fruit preservative. Satisfactory preservation effectiveness was observed for cherry tomato. Hydrothermal liquefaction of underutilized post-extraction residue was carried out. Temperature had limited impact on biocrude yield, but was crucial for biocrude quality. The effect of temperature and feedstock type were dependent on feedstock concentration. Abstract: Preservative is of importance to retard fruit deterioration and prolong the shelf-life. The suitability of using water-soluble polysaccharide extracted from waste macroalgae Enteromorpha prolifera (EPP) for cherry tomato preservation was evaluated. As compared with the control, the EPP-treated cherry tomatoes exhibited better fruit appearance, lower disease index and rot index during storage. Around 47 % EPP-treated cherry tomatoes were commercially acceptable after 36 days, which was however only 15.6 % for untreated cherry tomatoes, indicating the satisfactory preservation effectiveness of EPP-rich solution for cherry tomatoes. The post-extraction residue was commonly underutilized, we herein attempted to employ an emerging thermochemical conversion technique, hydrothermal liquefaction, to produce crude bio-oil (biocrude) from post-extraction E. prolifera . A biocrude yield of ∼23 wt% (dry-ash-free, daf) was obtained, and fatty acids and phenolics were identified to be the two main components in biocrude. The biocrude contained ∼70 % carbon and the higher heating value was ∼30 MJ/kg.